Crisis management in organizations (Regulatory approach) - Ahmed madasse; mostefa dassa (Social Empowerment Journal, 2021)
This scientific article aims to show that the crisisis not just an accidentalevent, but ratheracomplexdynamicprocessthatincludes a real threat to the entity and existence of the organization. Therefore, crisis management in the modern sensefocuses on the precise identification of obstacles and weaknesses, relying on a set of tools and mechanisms, whichrequirePaying attention to the levels of the organizational structure of the organization, and trying to impartsufficientorganizationalflexibility, to the variousoperations, and to avoiddysfunctionbased on humanerrors, in addition to rapid and adequateresponse to face crises, withdecisionsthat are subject to scientific support and correct information.